Peran pendidikan dalam memerangi korupsi: Komparasi Indonesia dan Hong Kong - Ary Patria Sanjaya; Irena Trifena (Integritas: Jurnal Antikorupsi, 2023)
Indonesia has been dealing with corruption for a long time. Several strategies are applied to address the complexities of corruption, one of which is anti-corruption education (ACE). Some countries have tried implementing ACE, with Hong Kong being one of the most successful. Using a comparative method, this study seeks to examine the impact of ACE on corruption, analyse how Hong Kong and Indonesia differ in implementing ACE, and develop suggestions for Indonesian leaders based on the best practices found in Hong Kong’s way of approaching ACE while still considering the Indonesian context. Improved collaborations among stakeholders (KPK, Ministries, and private parties), empowerment of schools and teachers, use of public media, and adequate political support are all found to be relevant to improving ACE in Indonesia.